2023
DOI: 10.1177/21582440231152403
|View full text |Cite
|
Sign up to set email alerts
|

Educational Vlogs: A Systematic Review

Abstract: This article presents a systematic review of the literature on the role of educational vlogging in enhancing learning and teaching outcomes. The researcher analyzed a total of 60 papers published from 2011 to 2021 using qualitative analysis with complementary quantitative analysis. The findings shed light on the vital role of vlogging in education over the last decade. This systematic review provides scholars and practitioners in the fields of education and educational technology with valuable information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Vlogging in the higher education sector Hassan's (2023) systematic review examined 60 recent papers exploring educational applications of vlogs across higher education and K-12 settings and found that vlogging could serve as an effective tool for reflection, instructional design and pedagogically to strengthen links between theory and practice. Hassan recommended that "future research may focus on the effectiveness of using vlogging to help pre-service teachers utilise and include multimedia as an integral part of the curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Vlogging in the higher education sector Hassan's (2023) systematic review examined 60 recent papers exploring educational applications of vlogs across higher education and K-12 settings and found that vlogging could serve as an effective tool for reflection, instructional design and pedagogically to strengthen links between theory and practice. Hassan recommended that "future research may focus on the effectiveness of using vlogging to help pre-service teachers utilise and include multimedia as an integral part of the curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the suggested benefits of vlogging, several challenges have been presented. Hassan (2023) identified technical difficulties and students' sense of vlogging as an atypical form of communication detached from their daily reality. Reeves et al (2017) revealed that students rarely rewatched their videos but preferred to watch the videos of their peers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section I will outline how examining relevant literature informed the create stage. According to Hassan (2023), vlogging has emerged as a popular form of digital media that has the potential to be a valuable educational tool. One of the primary benefits of educational vlogging is its potential to engage students and increase their motivation to learn (Mandasari & Aminatun, 2019).…”
Section: Understandmentioning
confidence: 99%